Effect of processing methods on nutritional, sensory, and physicochemical characteristics of biofortified bean flour - Nkundabombi, Marie G.; Nakimbugwe, Dorothy; Muyonga, John H. (Food science & nutrition, 2016)
Common beans (Phaseolus vulgaris L.) are rich, nutritious and affordable by vulnerable groups, thus a good choice for biofortification to address malnutrition. However, increasing micronutrients content of beans, without improving micronutrients bioavailability will not improve the micronutrients status of consumers. Effect of different processing methods on the physicochemical characteristics of biofortified bean flour was determined. Processing methods used in this study were malting (48 h), roasting (170°C/45 min), and extrusion cooking using a twin screw extruder with three heating sections, the first set at 60°C, the second at 130°C, and the last one at 150°C. The screw was set at a speed of 35 Hz (123 g) and bean flour moisture content was 15%. Mineral extractability, in vitro protein digestibility, pasting properties, and sensory acceptability of porridge and sauce from processed flour were determined. All processing methods significantly increased (P < 0.05) mineral extractability, iron from 38.9% to 79.5% for K131 and from 40.7% to 83.4% for ROBA1, in vitro protein digestibility from 58.2% to 82% for ROBA1 and from 56.2% to 79% for K131. Pasting viscosities of both bean varieties reduced with processing. There was no significant difference (P < 0.05) between sensory acceptability of porridge or sauce from extruded biofortified bean flour and malted/roasted biofortified bean flour. Acceptability was also not affected by the bean variety used.
Keywords: Extrusion cooking; iron biofortified beans; malting; mineral bioavailability; roasting